4OTumour cells mirror embryonic developmental programs to acquire invasive and metastatic capabilities. (7th November 2019) - Saghafinia, S; Michael, I; Homicsko, K; Hanahan, D
Abstract: Background: Pancreatic Neuroendocrine Tumours (PanNETs) are the second most common form of pancreatic cancer. We previously identified two principal subtypes of PanNET: insulinomas (islet tumors; IT) and metastasis-like primaries (MLP), corresponding to the low- and high-grade classification of human PanNETs. This study describes the mechanisms by which PanNETs progress from IT to more aggressive MLP tumors and eventually metastasize. Methods: We profiled single cell transcriptomes, bulk mRNA and miRNA transcriptomes and the proteomes of primary and metastasis specimens from the genetically engineered mouse model of PanNETs (Rip1 Tag2). Results: We found that the IT tumours maintained the expression of mature ß cell markers. In contrast, the MLP tumours expressed pancreatic progenitor markers. By integrating the data on ß-cell differentiation from pancreatic progenitors to mature ß cells, we demonstrated that the tumour progression from IT to MLP follows the reverse embryonic and postnatal developmental path. Furthermore, we identified Hmgb3 and miR-181cd cluster as the MLP master regulators. Over-expression of the miR-181cd cluster in IT-like cancer cell-lines resulted in the acquisition of the MLP gene signature and MLP morphologic phenotypes, in addition to activation Hmgb3 expression. This suggested a central role for Hmgb3 in initiating the MLP program. Furthermore, inhibiting the expression of Hmgb3 in MLP-like cancer cell-lines resulted in a significant growth decrease, demonstrating the importance of Hmgb3 in the maintenance of MLP-like cell state in vitro. Using transcriptomic data from human patients, we evaluated the relevance of the MLP program in human tumours. We established that aggressive human PanNET tumours also follow the same reverse developmental trajectory of dedifferentiation. Notably, patients with high MLP genes expression had a worse prognosis. Conclusions: These data demonstrate dedifferentiation as a mechanism by which malignant neuroendocrine cancer cells acquire progenitor-like features, enabling them to become more aggressive and metastatic. In addition, miR-181cd cluster and Hmgb3 act as the core regulators in the initiation of dedifferentiation and maintenance of progenitor-like features in tumour cells. Legal entity responsible for the study: CMSO Group at ISREC, EPFL. Funding: Swiss National Science Foundation. Disclosure: All authors have declared no conflicts of interest.